Roads and the Urban Environment : Proceedings of the Symposium on Roads and the Urban Environment held at the Ministry for Public Works in Madrid on 14th, 15th and 16th October 1974 (Paris : Organisation for Economic Co-operation and Development , Washington, D.C. : [sold by] OECD Publications Center, 1975)
This present program is primarily concerned with defining the scientific and technological basis needed to assist governments of member countries in decision-making on the most urgent road problems: traffic control systems, both in urban and rural areas; development and evaluation of integrated urban and suburban transport strategies; formulation, planning and implementation of common overall strategies for safety; and planning, design and maintenance of the total road infrastructure.
Includes bibliographical references.
ne 7/03/2018
Loans
Keywords: Roads; Automobiles; Traffic Noise